2020
DOI: 10.4142/jvs.2020.21.e49
|View full text |Cite
|
Sign up to set email alerts
|

Avian leukosis virus subgroup J and reticuloendotheliosis virus coinfection induced TRIM62 regulation of the actin cytoskeleton

Abstract: Background: Coinfection with avian leukosis virus subgroup J (ALV-J) and reticuloendotheliosis virus (REV) is common in chickens, and the molecular mechanism of the synergistic pathogenic effects of the coinfection is not clear. Exosomes have been identified as new players in the pathogenesis of retroviruses. The different functions of exosomes depend on their cargo components. Objectives: The aim of this study was to investigate the function of co-regulation differentially expressed proteins in exosomes on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In recent years, outbreaks of avian immunosuppressive and neoplastic diseases such as MD, AL, and RE have been frequently reported in chicken flocks worldwide, including in China [2,[9][10][11][13][14][15][20][21][22][23][27][28][29][30]. Especially during 2020-2022, a concentrated outbreak of suspected neoplastic diseases occurred in poultry farms from the South to North of China, but the main reasons remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, outbreaks of avian immunosuppressive and neoplastic diseases such as MD, AL, and RE have been frequently reported in chicken flocks worldwide, including in China [2,[9][10][11][13][14][15][20][21][22][23][27][28][29][30]. Especially during 2020-2022, a concentrated outbreak of suspected neoplastic diseases occurred in poultry farms from the South to North of China, but the main reasons remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, monoinfection of REV does not present apparent clinical symptoms and is mostly ignored. Once co-infected with other pathogens, especially with MDV and ALV-J, it shows obvious clinical symptoms and immunosuppressions, increases the incidence of tumours in infected chickens, and reduces the efficacy of other vaccines, which finally leads to more serious economic losses [20,21]. Currently, no effective vaccine is available for the prevention and control of REV either.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have shown that host proteins such as IRF7, MX1, TIMP3, and AKT1 may be related to the synergy of MDV and REV. In the coinfection of the Avian leukosis virus subgroup J (ALV-J) and REV, host protein TRIM62 increases replication of the two viruses by regulating the actin cytoskeleton [113].…”
Section: Viral Synergymentioning
confidence: 99%
“…The contents and specific regulatory roles of EVs are poorly described in the context of infectious diseases in chickens. The few studies that have characterized the contents of EVs in the context of immune responses in chickens focus primarily on miRNA profiles, with little focus on protein content; therefore, studies are required to evaluate the role of EV protein content in the induction and modulation in the host response to viral infections [19][20][21][22][23][24][25][26]. For example, a recent study evaluated the proteomic profile of serum exosomes from Marek's Disease Virus (MDV)-vaccinated and protected and lymphoma-bearing chickens and identified potential biomarkers for the disease [24].…”
Section: Introductionmentioning
confidence: 99%